Answer:
b = 5/12
Step-by-step explanation:
You have the proportion
1/(3b) = 4/5
Cross multiply to get rid of the fractions...
5 = 12b now solve for b
5/12 = b (divide by 12 on both sides)
Using product rule;
f(x)=(1+6x²)(x-x²)
f'(x)=(12x)(x-x²) + (1-2x)(1+6x²) = 12x² -12x³ +1 +6x² -2x -12x³ = -24x³ +18x² -2x +1
Solving the bracket first;
f(x)=(1+6x²)(x-x²) = x -x² +6x³ -6x^4
f'(x)= 1 -2x +18x² -24x³ = -24x³ +18x² -2x +1
PLS HELP ASAP I DONT HAVE TIME. IT ALSO DETECTS IF ITS RIGHT OR WRONG. SHOW PROOF. PLS HELP ASAP I DONT HAVE TIME. IT ALSO DETECTS IF ITS RIGHT OR WRONG. SHOW PROOF. PLS HELP ASAP I DONT HAVE TIME. IT ALSO DETECTS IF ITS RIGHT OR WRONG. SHOW PROOF. PLS HELP ASAP I DONT HAVE TIME. IT ALSO DETECTS IF ITS RIGHT OR WRONG. SHOW PROOF. PLS HELP ASAP I DONT HAVE TIME. IT ALSO DETECTS IF ITS RIGHT OR WRONG. SHOW PROOF. PLS HELP ASAP I DONT HAVE TIME. IT ALSO DETECTS IF ITS RIGHT OR WRONG. SHOW PROOF. PLS HELP ASAP I DONT HAVE TIME. IT ALSO DETECTS IF ITS RIGHT OR WRONG. SHOW PROOF. PLS HELP ASAP I DONT HAVE TIME. IT ALSO DETECTS IF ITS RIGHT OR WRONG. SHOW PROOF.
Given :
Two equations :
-8x + 3y = -17 ....1)
3x - y = 7 ....2)
To Find :
The solution of the system.
Solution :
Multiplying equation 2) by 3 and adding with equation 1), we get :
(-8x + 3y) + 3(3x - y) = -17 + 21
x = 4
Putting above value of x equation 2) we get :
12 - y = 7
y = 5
Therefore, solution of system is ( 4,5 ).